Pacemaker-induced atrial fibrillation reconsidered—associations with different pacing sites and prevention approaches - Kreimer, Fabienne; Gotzmann, Michael (Frontiers in Cardiovascular Medicine, 2024)
The incidence of atrial fibrillation (AF) is significantly higher in patients with pacemakers than in the general population, which could be due to patient characteristics and the diagnostic tool of the pacemaker in detecting atrial high-rate episodes and subclinical AF, but also to the pacemaker itself providing AF-promoting conditions.It is well known that high ventricular pacemaker burden increases the likelihood of AF occurrence. However, the sites of atrial and ventricular pacing may also influence the risk for AF. The conventional sites for atrial and ventricular pacing are in the right atrial appendage and in the right ventricular apex. However, growing evidence suggests that alternative pacing sites may be superior for the prevention of AF. Bachmann bundle pacing, for example, promotes interatrial excitation conduction, resulting in atrial synchronicity and a shorter total atrial activation time, which may be preventive for the occurrence of AF. Moreover, in recent years, new ventricular pacing sites have come into focus with His bundle and left bundle branch pacing. In addition to the hemodynamic and electrophysiological cardiac benefits, these new options may also offer benefits in the prevention of AF.This review provides an overview of pacing-induced AF mechanisms and the association with different pacing sites, as well as approaches for prevention of pacing-induced AF, highlighting different sites and modes of atrial pacing and the newer sites of ventricular pacing.